2023
DOI: 10.2147/idr.s412350
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Spectrum β-Lactamase and Carbapenemase-Producing Gram-Negative Bacteria and Associated Factors Among Patients Suspected of Community and Hospital-Acquired Urinary Tract Infections at Ayder Comprehensive Specialized Hospital, Tigrai, Ethiopia

Abstract: Background Little is known about bacteria that produce extended-spectrum beta-lactamases (ESBLs) and carbapenemase in patients with urinary tract infections (UTIs) in Tigrai, Ethiopia. The aim of this study was to describe the magnitude of ESBL- and carbapenemase -producing gram-negative bacteria among patients suspected of community- and hospital-acquired UTIs at a referral hospital in Tigrai, Ethiopia. Methods A cross-sectional study was conducted at Ayder Comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
2
0
0
Order By: Relevance
“…The results showed that 30.3% of the E. coli isolates and 43.4% of Klebsiella spp could be described as multi-drug-resistant isolates. This agreed with a study in Ethiopia, the MDR pattern was higher in Klebsiella spp (93.3%) than in E. coli (80.4%) [21]. In addition, Klebsiella spp was more common as an ESBL-producing UTI pathogen than E. coli (63.4% and 59.1%, respectively) in our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results showed that 30.3% of the E. coli isolates and 43.4% of Klebsiella spp could be described as multi-drug-resistant isolates. This agreed with a study in Ethiopia, the MDR pattern was higher in Klebsiella spp (93.3%) than in E. coli (80.4%) [21]. In addition, Klebsiella spp was more common as an ESBL-producing UTI pathogen than E. coli (63.4% and 59.1%, respectively) in our study.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, Klebsiella spp was more common as an ESBL-producing UTI pathogen than E. coli (63.4% and 59.1%, respectively) in our study. This finding agreed with other studies in different countries such as Ethiopia [21], and Saudi Arabia [22] by which Klebsiella spp was the most ESBL producer gram-negative microorganism with percentages of Klebsiella spp (86.7%) vs E. coli (52.2%), and Klebsiella spp (48.7%) vs E. coli (41.9%), respectively. There are limited oral options for treating ESBL-producing bacteria associated with UTI.…”
Section: Discussionsupporting
confidence: 92%